Pengembangan Kecerdasan Interpersonal Anak Usia Dini melalui Metode Bermain - Fauziah Nasution; Janatun Fadhilah; Nadia Chairy Batubara; Sapna Tanjung (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to examine the significance of developing interpersonal intelligence in early childhood as a fundamental basis for supporting their social, emotional, and cognitive growth. Interpersonal intelligence which involves the ability to understand and interact effectively with others plays a vital role in forming positive relationships, promoting cooperation, and resolving conflicts in a healthy way. Through an in-depth literature review, this study explores various strategies and approaches that can be implemented to foster interpersonal intelligence from an early age, such as play based activities, group interactions, and the application of specially designed curricula. The findings show that a warm and supportive environment, interactions that are sensitive to children's needs, and opportunities to interact in meaningful social activities greatly contribute to improving children's interpersonal abilities. Therefore, this study recommends the importance of including strategies for developing interpersonal intelligence in early childhood education programs in order to form individuals who are able to interact socially and emotionally well in the future.